Experimental models of dermatological diseases - O. N. Sergeeva; M. B. Aksenenko; Yu. F. Fefelova; E. Yu. Sergeeva; T. G. Ruksha (Бюллетень сибирской медицины, 2019)
This review presents analysis of experimental models of atopic dermatitis, psoriasis, skin symptoms of autoimmune systemic connective tissue diseases, and blistering skin diseases. Presented in the review are experimental models of atopic dermatitis which reproduce various stages and types of disease that allows the investigation of disease pathogenesis. Atopic dermatitis can develop spontaneously in Nc/Nga mice. There are atopic dermatitis models initiated by monoclonal IgE injection or epicutant sensitization under dermal barrier disfunction imitation. Genetically modified atopic dermatitis models - transgenic and knockout mice – are convenient for investigation of disease stages, cytokines, antigen-presenting cells and T-cells influence. We show that the psoriasis models created by genetic engineering methods are the most convenient for investigation of the role of particular cell types and specific factors in the disease development. Up-regulation of adhesion molecules, cytokines, transcription factors, inflammation mediators in both keratinocytes and immune cells of transgenic mice reveals their influence on psoriasis pathogenesis. There are descriptions of skin symptom models of autoimmune systemic connective tissue diseases and blistering skin disease models with and without genetic modifications. Each model demonstrates some peculiarities of pathogenesis and disease symptoms, whereas combined use of the models will allow to study the mechanisms of development of atopic dermatitis, psoriasis, blistering skin diseases and skin lesions under autoimmune systemic connective tissue diseases, that will contribute to the development of modern effective methods of treatment.